The Application of Functional Theory: Indonesian Presidential Debate - Wahyuningsih Wahyuningsih; Deli Nirmala (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2020)
Functional theory is a one of theories that are common used on the research of political debates in American campaign discourse. In the present article, Indonesian presidential debate is analyzed from the perspective of functional theory. The goal of this study is to analyze language function produced by candidates and to evaluate the applicability of functional theory in analyzing Indonesian presidential debate. The authors employ qualitative method in analyzing data. Supporting instruments in analyzing data were functional theory and political discourse analysis (PDA). PDA used in interpreting language function in political context. While, functional theory provides three functions, namely: attacks, defends, and acclaims. The finding shows that two different axioms are found. The first is the use of attack more than defense; it is line with the prediction of functional theory that has been tested in American political debate. Second, the use of acclaims less than attack, it differs in a way from the prediction of functional theory. Fundamentally, functional theory can be used as an instrument in analysis political debates in Indonesia even though the findings were not exactly consistence with the prediction. Thereby, the theory needs to be developed discursively.